2016
DOI: 10.1016/j.jvs.2015.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcomes of very elderly patients with critical limb ischemia who undergo distal bypass surgery

Abstract: A very elderly age should not preclude a patient from undergoing distal bypass surgery. A history of coronary artery disease, a nonambulatory status, and hypoalbuminemia, along with the Wound, Ischemia, and foot Infection classification for patients with tissue loss, should be carefully considered to obtain the most benefit from distal bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Some recent studies reported that very elderly patients who underwent surgical bypass had good clinical outcomes. 26, 27 Indeed, in actual clinical settings, selection bias may occur during the selection by surgeons of patients who should undergo bypass surgery. It is necessary to at least recognize the heterogeneity between biological and chronological age when treating elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies reported that very elderly patients who underwent surgical bypass had good clinical outcomes. 26, 27 Indeed, in actual clinical settings, selection bias may occur during the selection by surgeons of patients who should undergo bypass surgery. It is necessary to at least recognize the heterogeneity between biological and chronological age when treating elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…7, 13 On admission of CLI patients, we controlled their chronic ischemic pain with nonsteroidal anti-inflammatory drugs and opioid drugs, and administrated antibiotics prophylactically for infection in the tissue loss site. We routinely referred patients to the comfort care team and infection survey team of the hospital.…”
Section: Preoperative Managementmentioning
confidence: 99%
“…Most recently, a single-center study of 126 infrainguinal reconstructions found preoperative hypoalbuminemia was independently predictive of poor amputation-free survival in very elderly patients with critical limb ischemia. 27 Nonetheless, our study extends the prior work by evaluating the effects of preoperative hypoalbuminemia on outcomes of vascular surgery patients, specifically after OAR or EVAR, in a large, multi-institutional, nationally-validated database.…”
Section: Discussionmentioning
confidence: 73%
“…Smaller studies within the vascular surgery literature have looked at the effects of preoperative hypoalbuminemia on patient outcomes. 20,26,27 A single-center study of general and vascular procedures demonstrated that preoperative hypoalbuminemia was associated with surgical site infections. 26 Our study shows that hypoalbuminemia did not have any significant effect on wound complications, and this difference may be because general surgical patients undergoing a bowel resection were included in the former study and a lack of groin incisions in vascular surgical patients in our study.…”
Section: Discussionmentioning
confidence: 99%